Assessment rubrics, learning and academic well-being at university: a study in Neuro-physiotherapy from the study demands-resources model - García-Ros, Rafael; Ruescas-Nicolau, Maria-Arantzazu; Cezón-Serrano, Natalia; Sánchez-Sánchez, M. Luz (Anales de Psicología / Annals of Psychology, 2025)
The development of manual skills is essential in health sciences degrees. Based on the Study Demands-Resources (SDR) model, this paper analyzes how Physical Therapy students evaluate a set of assessment rubrics aimed at promoting the acquisition of manual skills in Neuro-physiotherapy, and their relationship with students’ academic engagement and burnout, satisfaction and learning outcomes. The participants were 218 undergraduates (average age 21.4 years) from a great Spanish university. The study analyzes the relationship and predictive capacity of three variable sets (socio-demographic, SDR, engagement and academic burnout) on satisfaction and academic achievement in the Neuro-physiotherapy subject. Pearson’s correlation coefficients and multiple hierarchical regressions were used for analysis. The rubrics’ usefulness for learning the manual skills involved is highly valued by students, a relevant issue considering their breadth, specificity and complexity. As expected, the SDR variables are correlated with engagement-burnout, and with satisfaction and academic results. The predictive and incremental validity of the different blocks of variables on both criteria, especially of engagement and academic burnout, is confirmed. The results emphasize the rubrics’ usefulness to promote students’ learning and academic satisfaction, as well as the determinant role of engagement and academic burnout on the students’ well-being, psychological functioning and learning outcomes.